Analysis of Landslide Hazard Levels on the Palopo – Luwu Road using GIS and Finite Element Method - Jawil, Anshar Abdullah; Setiawan, Kadek Nando (JURNAL GEOCELEBES, 2025)
Indonesia is one of the countries that often experiences landslides during the rainy season. The Palopo–Luwu main road is a landslide-prone area in North Bastem sub-district because it has a topographic condition with a very steep slope. Therefore, it is important to conduct research on the analysis of the potential for landslides in the area. The method used in this study is Weighted Overlay based on Geographic Information Systems (GIS) in making landslide-prone maps. Data processing with weighting or scoring on parameters such as slope, rainfall, rock type, soil type, and land cover. While the Finite Element Method (FEM) is used to model slope stability with input data on physical and mechanical properties of rocks and slope geometry data as a basis for calculating the slope safety factor (FK). The results of the study showed that almost 85% of the research area is a high landslide potential area which is the Palopo–Luwu main road area, this was validated from laboratory test data which was then analyzed for slope stability showing FK value <1.25, which is 0.936 and the actual condition of the slope in the field has collapsed. The mapping results can be used as a useful tool for land use planning and risk reduction in the research area.